Walk two moons [compact disc, unabridged] - Creech, Sharon (Listening Library, 2001)
After her mother leaves home suddenly, thirteen year-old Sal and her grandparents take a car trip retracing her mother's route. Along the way, Sal recounts the story of her friend Phoebe, whose mother also left.